Implementasi PP Nomor 55 Tahun 2022 terhadap PPh Pasal 4 ayat (2) pada CV MSM (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research is prepared with the aim of analyzing the implementation or application of PP Number 55 of 2022 on the reporting of Article 4 Paragraph (2) Income Tax at CV MSM. This research uses a descriptive qualitative approach utilizing data sources from financial statements, tax documentation, and interviews. The research results show that CV MSM, as a small and medium-sized enterprise with an annual turnover below IDR 4.8 billion, has fulfilled its tax obligations in accordance with the provisions of PP 55 of 2022. The total gross income from March to December 204 amounted to Rp3,374,588,245, with an outstanding income tax of Rp16,872,941. CV MSM has recorded transactions neatly, paid taxes on time, and calculated taxes accurately. The implementation of PP 55 of 2022 provides administrative ease and legal certainty and encourages tax compliance, thereby supporting the role of MSMEs in increasing state revenue.